Improving smallholder farmer adoption of climate smart agriculture practices - Margiotta, Sarah; Giller, Onno (Climate Change, Agriculture and Food Security (CCAFS), 2010)
The International Institute of Tropical Agriculture (IITA), as part of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), with CIAT, Sustainable Food Lab and Rainforest Alliance, are promoting increased smallholder coffee farmer adoption of Climate Smart Agriculture (CSA) practices in Uganda. Initial IITA research on coffee began in 2010 and has subsequently expanded across 17 districts, 899 farmers, 51 on-farm field trials and 26 demonstration sites. IITA collaborates with Hanns R. Neumann Stiftung (HRNS) in Robusta coffee in Luwero and Olam, Kawacom and Great Lakes Coffee in Arabica coffee growing regions in Uganda. CSA practices in coffee are practices such as planting shade trees and soil and water conservation structures, that are fine tuned to the local context. Research concluded that CSA adoption is hindered, in part, due to limited resources and differing levels of entrepreneurship amongst smallholder coffee farmers in Uganda. In addition, farmer limitations and aspirations, farming systems, and climate change impact vary from site to site. Enablers of CSA adoption therefore need to be contextually specific to ensure they relate to local needs. A suite of studies have been conducted to explore the diversity in Uganda’s smallholder coffee farmers, their ranking of constraints to implementing CSA practices, and land use mapping to identify different ecological zones within a district.